2011
DOI: 10.3746/jkfn.2011.40.1.094
|View full text |Cite
|
Sign up to set email alerts
|

Quality Properties of Fermented Squid Viscera Product with Aspergillus oryzae Koji and Its Seasoning

Abstract: Squid (Todarodes pacificus) is processed as dried or seasoned-dried products and its catch gradually increased from 270,298 M/T in 2005 to 367,940 M/T in 2008 in Korea. Squid processing by-product (viscera) was usually discarded as a waste resulting in environmental problem. In order to utilize squid viscera for more value-added products, a natural squid seasoning was developed by fermenting with Aspergillus oryzae koji. Squid viscera at 5, 10 and 15% salt concentrations with fixed levels of 5% koji and 30% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…10.0, SPSS, Chicago, IL, USA), significant difference less than 5 percent (P<0.05) for the average value was researched. The study results indicated the average value and the standard deviation (Choi & Kim 2011).…”
Section: Discussionmentioning
confidence: 92%
“…10.0, SPSS, Chicago, IL, USA), significant difference less than 5 percent (P<0.05) for the average value was researched. The study results indicated the average value and the standard deviation (Choi & Kim 2011).…”
Section: Discussionmentioning
confidence: 92%
“…오징어 식해의 구성아미노산 및 유리아미노산 조성은 (27). 식해 맛은 유리아미노산 및 핵산 관련물질이 주 역할 을 하고 여기에 유기산, 유리당 및 향신료 성분 등이 보조적 맛 의 역할을 한다.…”
Section: 구성 및 유리아미노산unclassified